2019
DOI: 10.1016/j.celrep.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Reverses Behavioral and Synaptic Abnormalities after Maternal Inflammation

Abstract: Graphical Abstract Highlights d MIA causes behavioral and synaptic abnormalities in the offspring d Microglia-dependent synaptic engulfment is impaired by MIA d Voluntary running in adulthood ameliorates MIA-induced abnormalities d Voluntary running stimulates microglia-mediated engulfment of surplus synapses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 51 publications
0
57
1
1
Order By: Relevance
“…For example, embryonic inflammation and adolescent stress are shown to inhibit dendritic growth, induce neuronal remodeling and impaired synaptic transmission and plasticity, and lead to cognitive impairment in the aged mice ( Lesuis et al, 2019 ; Tellez-Merlo et al, 2019 ; Wang et al, 2020 ). In contrast, an adolescent EE can partly reverse behavioral and synaptic abnormalities resulting from embryonic inflammation ( Andoh et al, 2019 ). Under normal circumstances, Staufen is implicated in the transport and regulation of dendritic mRNA, so downregulation of Staufen expression can lead to a significant reduction in the number of dendritic spines and miniature excitatory postsynaptic currents, which are generally assumed to contribute to impaired synaptic plasticity ( Goetze et al, 2006 ; Popper et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, embryonic inflammation and adolescent stress are shown to inhibit dendritic growth, induce neuronal remodeling and impaired synaptic transmission and plasticity, and lead to cognitive impairment in the aged mice ( Lesuis et al, 2019 ; Tellez-Merlo et al, 2019 ; Wang et al, 2020 ). In contrast, an adolescent EE can partly reverse behavioral and synaptic abnormalities resulting from embryonic inflammation ( Andoh et al, 2019 ). Under normal circumstances, Staufen is implicated in the transport and regulation of dendritic mRNA, so downregulation of Staufen expression can lead to a significant reduction in the number of dendritic spines and miniature excitatory postsynaptic currents, which are generally assumed to contribute to impaired synaptic plasticity ( Goetze et al, 2006 ; Popper et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…resulting from embryonic inflammation (Andoh et al, 2019). Under normal circumstances, Staufen is implicated in the transport and regulation of dendritic mRNA, so downregulation of Staufen expression can lead to a significant reduction in the number of dendritic spines and miniature excitatory postsynaptic currents, which are generally assumed to contribute to impaired synaptic plasticity (Goetze et al, 2006;Popper et al, 2018).…”
Section: The Association Between Altered Staufen Expression and Cognimentioning
confidence: 99%
“…Seizure-like EEG signals have also been confirmed to occur in the cerebral cortex and hippocampus in AD model mice [7]. Furthermore, neuronal activity is increased in animal models of multiple sclerosis (MS), Parkinson's disease (PD) and autism spectrum disorders (ASDs), brain diseases that are sometimes accompanied by epileptic seizures [8][9][10][11][12]. Thus, it is likely that synaptic E/I imbalance is the main cause of epilepsy, but whether glial cells are involved has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that neuronal activity modulates synaptic properties through microglial activation both in physiological and pathological conditions . Our neuronal culture includes few microglia, thus, it can be assumed that neuronal activity directly affects synapse density.…”
Section: Resultsmentioning
confidence: 99%